Eksistensi Perlindungan Hukum Terhadap Anak Sebagai Akibat Tindak Pidana Pencabulan di Kabupaten Gianyar - Putu Dyah Agung Mas Narayana Putri; I Made Sepud; I Wayan Werasmana Sancaya (Warmadewa Press, 2024)
Children have limitations in understanding and protecting themselves from various influences of the existing system. When children are involved in legal issues, the state must provide protection to children through laws and regulations including Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. Sexual intercourse with children is an act that is categorized as rape and obscenity, and usually sexual intercourse is carried out by adults to children under the age of 15, therefore the formulation of the problem is raised, namely: 1) What is the legal protection against child victims of sexual abuse in Gianyar Regency? and 2) What are the criminal sanctions against perpetrators of criminal acts of child molestation in Gianyar Regency? This study uses an empirical research type. The results obtained from legal protection for child victims of abuse are that they have received legal protection as stipulated in Law No. 35 of 2014 on amendments to Law No. 23 of 2002 concerning Child Protection. Criminal sanctions obtained by perpetrators of child abuse are a minimum of 3 years and a maximum of 15 years in prison and a minimum fine of Rp. 60 million and a maximum of Rp. 300 million.